Tijdens het bespreken van de begroting van Sociale Zaken. V.l.n.r. : Dales, Den Uyl, d'Ancona - Naeff, Nico
Tijdens het bespreken van de begroting van Sociale Zaken. V.l.n.r. : Dales, Den Uyl, d'Ancona.